'I was born in the reign ...': Historical orientation in Ugandan students' national narratives (UCL Press, 2017)
In 2012, Uganda celebrated 50 years as an independent state following more than half a century under colonial rule. Since independence, Uganda has experienced a period of political turmoil and civil war within its constructed colonial borders. Given these historical experiences, what do students find important about their nation's history and what history do they relate to when asked to explain their contemporary society and envisage possible futures? This article argues that Ugandan students' historical orientation is informed by and dependent on these students' local contexts. Furthermore, those students adopting a retrospective approach to history, compared with those applying a prospective approach, made more sophisticated judgements about the past. The study on which this article is based explores 219 narratives written by 73 Ugandan upper secondary students. The narratives were elicited through written responses to three assignments and were designed to capture different approaches to history, specifically prospective and retrospective approaches. Participants originated from two distinct regions: central and northern Uganda. The empirical results show how different approaches to history influence the students' narratives. For instance, value judgements about past developments were more common among students applying a retrospective approach. Students from northern Uganda were generally more inclined to tell a story of decline.